Lisinopril Preserves Physical Resilience and Extends Life Span in a Genotype-Specific Manner in Drosophila melanogaster. (14th June 2019) - Gabrawy, Mariann M; Campbell, Sarah; Carbone, Mary Anna; Morozova, Tatiana V; Arya, Gunjan H; Turlapati, Lavanya B; Walston, Jeremy D; Starz-Gaiano, Michelle; Everett, Logan; Mackay, Trudy F C; Leips, Jeff; Abadir, Peter M
Abstract: Physical resiliency declines with age and comorbid conditions. In humans, angiotensin-converting enzyme (ACE) has been associated with attenuation of the decline in physical performance with age. ACE-inhibitor compounds, commonly prescribed for hypertension, often have beneficial effects on physical performance however the generality of these effects are unclear. Here, we tested the effects of the ACE-inhibitor Lisinopril on life span, and age-specific speed, endurance, and strength using three genotypes of the Drosophila melanogaster Genetic Reference Panel. We show that age-related decline in physical performance and survivorship varies with genetic background. Lisinopril treatment increased mean life span in all Drosophila Genetic Reference Panel lines, but its effects on life span, speed, endurance, and strength depended on genotype. We show that genotypes with increased physical performance on Lisinopril treatment experienced reduced age-related protein aggregation in muscle. Knockdown of skeletal muscle-specific Ance, the Drosophila ortholog of ACE, abolished the effects of Lisinopril on life span, implying a role for skeletal muscle Ance in survivorship. Using transcriptome profiling, we identified genes involved in stress response that showed expression changes associated with genotype and age-dependent responsiveness to Lisinopril. Our results demonstrate that Ance is involved in physical decline and demonstrate genetic variation in phenotypic responses to an ACE inhibitor.